Interchange : English for international communication - Richards, Jack C. (New York Cambridge university press, 1997)
This is the teacher's manual for "Interchange", level three. "Interchange" is a three-level course for learners of English as a foreign language. The course reflects the interests and needs of adults and young adults, taking them from beginning to high intermediate level.
Keywords: English language -- Grammar -- 1950-; English language -- Grammar; English language -- Usage